Health-promoting lifestyle and its predictors among health-related and non-health-related university students in Taiwan: a cross-sectional quantitative study - Dan-Ping Chao (BMC, 2023)
Abstract Background University students majoring in different disciplines are believed to have different personality traits, courses exposure, and future roles, which may further affect their health behaviors and health status. The purpose of this study was to investigate the differences in health-promoting lifestyle (HPL) and its predictors among health-related and non-health-related students. Methods The research participants were university students in the main island of Taiwan, and a two-stage sampling approach was adopted to obtain the samples from November 2020 to March 2021. First, 37 universities were randomly selected based on the ratio of public and private universities in each region of Taiwan. Then, based on the ratio of health-related and non-health-related majors of selected university, 25-30 students were randomly drawn from each university according to the student ID number to complete self-administered questionnaires, which included items for personal factors, perceived health status (PHS), health conception (HC), and health-promoting lifestyle profile (HPLP). A total of 1062 valid questionnaires were recovered, including 458 from health-related students and 604 from non-health-related students. Chi-squared test, independent samples t-test, one-way ANOVA, Pearson product-moment correlation analysis, and multiple regression analysis were performed. Results The results showed that gender (p < 0.001), residential status (p = 0.023), body mass index (p = 0.016), and daily sleep duration (p = 0.034) of the students majoring in different disciplines were different. Health-related students having better HC (p = 0.002) and HPLP (p = 0.040) than non-health-related students. In addition, for both majors, females, low PHS scores, and low scores for functional/role, clinical, and eudaimonistic dimensions of HC were important indicators of a relatively negative HPLP, while health-related students who exercised 75 min or less per week and non-health-related students with a monthly disposable income of 15,000 TWD or less or who dined out 15 times or more per week also required attention in the promotion of HPL (health-related majors: adjusted R2 = 0.481, p < 0.001; non-health-related majors: adjusted R2 = 0.443, p < 0.001). Conclusions Students majoring in each discipline who had poor HPLP which is mentioned above should be prioritized in the provision of appropriate exercise or nutritional support programs on campus to promote their awareness and ability to pay attention to their health.